Floristic Composition, Life-forms and Chorotypes of Plants for Extended Area from Aqan to Al-Erais, Lahej Governorate, Yemen - Atif, Mazen Alawi Ali Salim; Al-Super, Ahmed Mohammed Moqbal; Al-Hawshabi, Othman Saad Saeed (Journal of natural sciences, life and applied sciences, 2024)
The present study deals with the floristic analysis of the flora of parts two districts Al-Musemier and Tuban for the region extended between Aqan and Al-Erais, during the period from March 2020 to December 2022, the present study revealed that the about 208 taxa (including species and infra-specific taxa) belong to 132 genera and 48 families. The monocots are represented by 5 families, while the dicots represented by 43 families. The largest families are: Fabaceae (26 species), following by Poaceae and Euphorbiaceae (13 species for both), then Amaranthaceae, Apocynaceae and Solanaceae (12 species for each one). The largest genera recorded among the study area are: Acacia and Heliotropium (7 species for each). The most dominant life form are: Chamaephytes (79 species), with (37.98%), followed by Therophytes (60 species, 28.85%) and Phanerophytes (41 species, 19.71%). Datura ferox is added to the flora of Yemen, the first time. The aquatic plants and high moisture of soils are represented by 9 species belonging to 8 families. Five taxa are endemic to flora of Yemen; another eleven taxa are found to be near endemic to the flora of Yemen. Analysis of the Phyto-geographical data proved that the Sudano-Zambezian elements are the dominant elements among the flora of study area.